The effects of web-based learning experience, perceived-initiative, and perceived-performance on learners' attitudes toward mobile learning. (18th October 2007) - Yen, Jung-Chuan; Chen, Ming-Puu
This study explored the effects of prior web-based learning experience, perceived-initiative, and perceived-performance on learners' attitudes toward a mobile learning system designed to enhance novices' reflective thinking and problem-solving through reflection-in-action. Instructional simulations for Linux Fedora system installation were provided via mobile devices to facilitate novices' learning of Fedora system. A learner's reflective thinking was enhanced by responding to the reflection prompts and summarising what one had learnt from the encountered erroneous actions during instructional simulations. The results revealed that the learners showed positive attitudes toward mobile learning, and the initiative learners showed more positive attitude in willingness-to-use, ease-of-use, and helpfulness toward mobile learning than the less initiative ones. It was concluded that a well-designed mobile learning system not only possesses the potentiality to facilitate learners' reflective thinking, but also captures the hearts of learners.